Academician V. Peresypkin - founder of the Southern Department of Agricultural Sciences - Nyzhnyk, S. V. (History of science and technology, 2014)
Article by historical and scientific analysis highlights the activities of the Southern Branch of the All-Union Academy of Agricultural Sciences Lenin (1969 - 1972) under the guidance of renowned plant pathologist scientist V. Peresypkin. Reflects the main achievements and shortcomings in scientific guidance department.